2020
DOI: 10.1155/2020/8735190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of New Analogs of Hexyloxy Phenyl Imidazoline on Quorum Sensing in Chromobacterium violaceum and In Silico Analysis of Ligand-Receptor Interactions

Abstract: The increasing common occurrence of antibiotic-resistant bacteria has become an urgent public health issue. There are currently some infections without any effective treatment, which require new therapeutic strategies. An attractive alternative is the design of compounds capable of disrupting bacterial communication known as quorum sensing (QS). In Gram-negative bacteria, such communication is regulated by acyl-homoserine lactones (AHLs). Triggering of QS after bacteria have reached a high cell density allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Imidazoline 32b was QSI at all concentrations and displayed IC 50 = 65.09 µM. The QS inhibition activity of 32b is comparable to other synthesized bioisosteres [ 21 ]. Imidazoline 32c at 1000 μM afforded 46% activity and compound 32a behaved as an antimicrobial at the latter concentration.…”
Section: Evaluation Of Qs Inhibition On Chromobacterium mentioning
confidence: 64%
See 2 more Smart Citations
“…Imidazoline 32b was QSI at all concentrations and displayed IC 50 = 65.09 µM. The QS inhibition activity of 32b is comparable to other synthesized bioisosteres [ 21 ]. Imidazoline 32c at 1000 μM afforded 46% activity and compound 32a behaved as an antimicrobial at the latter concentration.…”
Section: Evaluation Of Qs Inhibition On Chromobacterium mentioning
confidence: 64%
“…Furthermore there are reports of its replacement with cyclopentane, cyclopentanol, cyclopentanone, oxazolidinone, benzothiazol and thiadiazol [ 13 ]. Our group reported a substitution with imidazoline and oxazoline in prior studies [ 20 , 21 ]. In the design of the present bioisosteres, the amido group and the lateral chain were conserved but the length of the latter varied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These promising natural-based hits exhibit preferential polar interactions with Trp84, Asp97, Met135, and Ser155, in addition to relevant hydrophobic contacts towards Tyr80, Leu85, Tyr88, Met89, Trp111, Phe115, and Phe126, which have been successfully translated into high biological findings. Comparable residue-wise binding interactions were reported for several chemically synthesized 2-imidazoline/oxazoline-based analogues through molecular docking and dynamics simulations [59]. The compounds predict favourable polar binding contributions for Trp84, Asp97, Tyr88, Ser155, and Pro189 residues with the ligands' 2-imidazoline/oxazoline polar heads.…”
Section: Discussionmentioning
confidence: 85%
“…Another study showed promising CviR-based anti-virulence biological activity for flavonoid- and chalcone-based hits, predicting favorable polar interactions with Trp84, Asp97, Met135, and Ser155, as well as non-polar contacts to Tyr80, Leu85, Tyr88, Met89, Trp111, Phe115, and Phe126 [ 59 ]. Comparable residue-wise bindings were also demonstrated for several synthetic oxazoline/2-imidazoline-based derivatives through molecular docking-coupled dynamics simulations [ 60 ]. Similarly, isolates from Passiflora edulis showed the relevant accommodation of the CviR binding site which is mediated through balanced hydrophilic–hydrophobic contacts with Ile57, Tyr80, Tyr84, Leu85, Tyr88, Ile99, Trp111, Phe115, Met135, and Ile153 [ 61 ].…”
Section: Discussionmentioning
confidence: 99%